Performance of sewage treatment plant with septic tank, anaerobic filter and constructed wetland with Typha spp - Neto, Paulo Fortes (2020)
The study reports the performance of a sanitary effluent treatment constituted by a septic tank, anaerobic filter and constructed wetland. The study monitored nutrient’s, carbonaceous material’s and thermotolerant coliform’s (CT) removal efficiency during 12 months. The treatment system included a septic tank, an anaerobic filter and a horizontal subsurface flow constructed wetland cultivated with Typha spp. Effluent samples were monthly collected before and after the septic tank, anaerobic filter and wetland. The removal efficiency for N-NH+4 was 37.6%, 66.3% for total P, 37% for COD, 54% for BOD and 99.4% for CT. The anaerobic filter and wetland were more efficient than the septic tank. P-total reduction was higher in the constructed wetland than in the anaerobic filter. Climatic conditions influenced the evaluated constituent’s removal being the highest values during hot months